Intercepting Dementia: Awareness and Innovation as Key Tools - Brai, Emanuele; Tonacci, Alessandro; Brugada-Ramentol, Victòria; D’Andrea, Federica; Alberi, Lavinia (Frontiers in Aging Neuroscience, 2021)
Dementia is a common feature of several age-related brain diseases, leading to a progressive cognitive decline. Due to a growing aging rate, dementia-related disorders currently affect around 50 million people worldwide and by 2050 this number is expected to reach 150 million. Additionally to patients, these neurodegenerative pathologies have a strong impact on family members, caretakers and other health professionals, therefore representing a public health burden that in 2020 accounted for over 1 trillion USD and projected to double in the next decade. To overcome this devastating condition, many organizations and collaborative networks sustain that only a complete understanding of dementia in its different characteristics can drive the scientific community towards the development of effective therapeutic approaches aiming at preventing the onset and halting its progression. In this work, we discuss two topics that represent fundamental resources in fighting dementia: i) the importance of raising awareness about this condition to avoid stigma and gauging investment, and ii) the introduction of novel screening measures to prevent and potentially revert cognitive decline. Finally, we discern how knowledge-based advocacy will help the rollout of clinical trials and the development of novel and timely pharmacological interventions.